The role of artificial intelligence applications and their impact on improving the quality of external auditing : A field study of a group of auditors (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The research aims to identify the role of artificial intelligence techniques in improving the quality of external auditing in the Federal Board of Financial Supervision as a result of the development in the external auditing profession witnessed by the Iraqi environment. To achieve the research objective, a questionnaire consisting of (13) questions was designed and distributed to the research sample (91) samples. The research reached conclusions, the most important of which was that the application of artificial intelligence dimensions has a significant impact on improving the quality of external auditing. The most important recommendations are the need for the Federal Board of Financial Supervision to pay attention to artificial intelligence techniques to analyze financial data.